ANALISIS KESENJANGAN KESEJAHTERAAN BURUH TANI SAWAH DI DESA BATU PUTIH KABUPATEN OGAN KOMERING ULU - Putri Ayu Ogari; Ema Pusvita (JURNAL AGRIBISNIS TERPADU, 2021)
This research is entitled "Gap Analysis of Welfare of Farmers in the Rice Fields in Batu Putih Village, Ogan Komering Ulu Regency". This study aims to determine the factors that occur in the level of disparities in the welfare level of rice field farm workers in Batu Putih Village, Ogan Komering Ulu Regency. This study uses a simple random sampling method (Simple Random Sampling). Methods of data analysis using Gini ratio and discriminant regression analysis. The results of this study are the factors that influence the disparities in the welfare of rice field farm workers in Batu Putih Village are the income variable (PD) α of 22.7 percent, the education level (TP) α of 0.52 percent, the number of family workers (JKB). α by 13.4 percent and middleman loan (PT) α by 18.6 percent.